Hantavirus Infection Is Inhibited by Griffithsin in Cell Culture - Shrivastava-Ranjan, Punya; Lo, Michael K.; Chatterjee, Payel; Flint, Mike; Nichol, Stuart T.; Montgomery, Joel M.; O'Keefe, Barry R.; Spiropoulou, Christina F. (Frontiers in Cellular and Infection Microbiology, 2020)
Andes virus (ANDV) and Sin Nombre virus (SNV), highly pathogenic hantaviruses, cause hantavirus pulmonary syndrome in the Americas. Currently no therapeutics are approved for use against these infections. Griffithsin (GRFT) is a high-mannose oligosaccharide-binding lectin currently being evaluated in phase I clinical trials as a topical microbicide for the prevention of human immunodeficiency virus (HIV-1) infection (ClinicalTrials.gov Identifiers: NCT04032717, NCT02875119) and has shown broad-spectrum in vivo activity against other viruses, including severe acute respiratory syndrome coronavirus, hepatitis C virus, Japanese encephalitis virus, and Nipah virus. In this study, we evaluated the in vitro antiviral activity of GRFT and its synthetic trimeric tandemer 3mGRFT against ANDV and SNV. Our results demonstrate that GRFT is a potent inhibitor of ANDV infection. GRFT inhibited entry of pseudo-particles typed with ANDV envelope glycoprotein into host cells, suggesting that it inhibits viral envelope protein function during entry. 3mGRFT is more potent than GRFT against ANDV and SNV infection. Our results warrant the testing of GRFT and 3mGRFT against ANDV infection in animal models.